Afterlife as Motivation for Later Life Education among Elderly Women: Evidence from Bauchi Emirate North-Eastern Nigeria - Kabiru Aminu Garba; Abubakar Yakubu (Tafkir: Interdisciplinary Journal of Islamic Education, 2022)
This study explores the motivation for later life education among elderly women (60+) in Northeastern Nigeria. Intrinsic and extrinsic dimensions of motivation were explored in relation to personal, historical, and institutional influences based on an orientation of Activity, Life-course, and Gerotranscendence theories. To achieve the research aims, three research questions were posed.  First, what are the historical and institutional basis of motivation for later life education among elderly women? Secondly, how do intrinsic and extrinsic dimensions of motivation influence later life education among elderly women? Thirdly, how can improvement in later life education result in better coping among elderly women? Information was obtained using qualitative methods. Findings reveal that extrinsic motivation stems from historical links between Bauchi Emirate and Sokoto Caliphate as a center for Islamic civilization. Further, since the social institutions in the Bauchi emirate were a replication of the model of society promoted by the Jihad and the caliphate administration, later life education among elderly women is encouraged. As evident from the data generated on personal motivation factors, the majority of elderly women see later life education as an important coping prerequisite arising from intrinsic motivation with the most common reasons given as spiritual and religious benefits. A major finding of the present study relates to how motivation for later-life learning is regarded as a means of perfection in spiritual engagement for a successful transition to the afterlife. The study offers a number of recommendations for improved motivation for later life education among elderly women.